Factors for the decline of ADL before and after the COVID-19 of people with dementia in Japan - Taiga Fuju; Natsumi Shinya; Kumiko Yamada; Reiko Oshima; Taiki Yoshita; Naoya Tsukii; Yuta Ishimitsu; Naoto Okonogi; Yukiko Tanaka; Tomoyuki Shinohara (Archives of Gerontology and Geriatrics Plus)
Background: This study aimed to investigate the determinants of decline in activities of daily living (ADL) among people with dementia following the onset of the coronavirus disease of 2019 (COVID-19). Methods: A retrospective analysis was performed, including 37 individuals with dementia residing in group and nursing homes. The study cohort experienced a resurgence in facility admissions following COVID-19 outbreak, spanning from September to December 2022. Multivariate generalized linear mixed-effects models were employed to assess the Barthel Index at the time of readmission, which served as the dependent variable. Demographic variables before contracting COVID-19 were considered independent predictors if they were significantly associated with the Barthel Index at the time of readmission. Random intercepts were applied to account for variations among facilities in which individuals resided before contracting COVID-19. Results: Care level, degree of independent living for disabled older adults, and the ability to perform daily ambulatory movements were significantly associated with the Barthel Index at the time of readmission. When used as independent variables, both daily ambulatory movement (beta = 0.350) and care level (beta = -0.347) showed significant associations with the Barthel Index at the time of readmission. Whereas using daily ambulatory movements and the degree of independent living for disabled older adults as independent variables, only the degree of independent living for disabled older adults (beta = -0.757) was significantly associated with the Barthel Index at the time of readmission. Conclusion: The ability to engage in daily ambulatory movement affects the decline in ADLs due to COVID-19.